Penurunan Kadar Bahan Organik dan Proksimat pada Air Budidaya Ikan Lele (Clarias gariepinus) Menggunakan Bacillus subtilis - Sri Intan Anggraini; Diana Arfiati; Happy Nursyam; Audina I. Pratiwi; Ekki Windi; Sofiatul (Samakia : Jurnal Ilmu Perikanan, 2019)
To reduce organic waste in catfish maintenance media (Clarias gariepinus) and waste management wastes a cultivation management technology is needed, one of these technologies is bioremediation using Bacillus subtilis as a bioremediator. This study aims to analyze the parameters of organic matter content including TOM (Total Organic Matter), Protein, Carbohydrates and Fat. The study was conducted in January-February 2019. This study used a factorial completely randomized design (Factorial RAL) with the addition of Bacillus subtilis 4 treatments including controls (K = Control, D1 = 100 ml / L, D2 = 10 ml / L and D3 = 1 ml / L) at 24th, 48th, 72nd, 96th and 120th hours, consisting of three replications. The results obtained from this study indicate that the concentrations of each parameters in treatments D1, D2 and D3 were lower than those of controls, indicating that Bacillus subtilis can reduce organic waste from catfish ponds. The best treatment was W5D2 as bioremediation of catfish organic waste with the remaining TOM 16.23% with an efficiency value of 84%, remaining protein 86.66% with an efficiency value of 13%, remaining carbohydrate 63.91% with an efficiency value of 36% and remaining Fat 52.69% with an efficiency value of 47%.